1985
DOI: 10.1111/1540-6229.00338
|View full text |Cite
|
Sign up to set email alerts
|

Public Information and Abnormal Returns in Real Estate Investment

Abstract: This study performs empirical tests of the semistrong form efficiency of a real estate investment market. An asset pricing model is utilized to estimate the abnormal returns resulting from two types of public information, major changes in government tax shelter and rent control policies as well as unanticipated changes in interest rates. In both cases the results find an absence of significant abnormal returns and no evidence to suggest that real estate investors can utilize information concerning government p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 18 publications
0
27
1
1
Order By: Relevance
“…They also applied statistical methodology of the RWH in investigating single -family residential prices. This study shows advancement in its evaluation of the market when compared to that of analysis of Gau ( ,1985 who tested the weak form efficiency of residential markets using Canada as evidence and reported that Canadian income generating residential markets are efficient. Case and Shiller results did not confirm the presence of weak form efficiency for housing markets this was contrary to the study of Gau ( ,1985 and Linneman (1986).…”
Section: Empirical Evidence On Market Efficiencymentioning
confidence: 95%
See 1 more Smart Citation
“…They also applied statistical methodology of the RWH in investigating single -family residential prices. This study shows advancement in its evaluation of the market when compared to that of analysis of Gau ( ,1985 who tested the weak form efficiency of residential markets using Canada as evidence and reported that Canadian income generating residential markets are efficient. Case and Shiller results did not confirm the presence of weak form efficiency for housing markets this was contrary to the study of Gau ( ,1985 and Linneman (1986).…”
Section: Empirical Evidence On Market Efficiencymentioning
confidence: 95%
“…This study shows advancement in its evaluation of the market when compared to that of analysis of Gau ( ,1985 who tested the weak form efficiency of residential markets using Canada as evidence and reported that Canadian income generating residential markets are efficient. Case and Shiller results did not confirm the presence of weak form efficiency for housing markets this was contrary to the study of Gau ( ,1985 and Linneman (1986). By applying exchange tactics to further proof the absence of the weak form efficiency for US single-family homes Case and Shiller (1989) highlight uncertainties as proof of whether or not housing markets are efficient.…”
Section: Empirical Evidence On Market Efficiencymentioning
confidence: 95%
“…However, Gau (1985) points out some caveats with respect to data problems inherent in his study. Linneman (1986) focuses his study on the efficiency of the housing market on the housing market of Philadelphia for two points in time (1975 and 1978) using observations on individual homeowner assessments of their house values.…”
Section: Literature Reviewmentioning
confidence: 96%
“…His results are in support of the random walk-fair game model and thus, in support of the weak-form version of the efficient market hypothesis. In a subsequent study by Gau (1985) -based on the same series of apartment transactions from 1971 to 1980 as in Gau (1984) -the semi-strong form version of the efficient market hypothesis is considered by applying the asset pricing framework of the capital asset pricing model and the arbitrage pricing theory. These models are utilized to estimate the abnormal returns resulting from two types of public information, major changes in government tax shelter and rent control policies as well as unanticipated changes in mortgage interest rates.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation